The Analysis of Campaign Strategy and Victory in the 2024 Kerinci Regency DPRD Legislative Election: A Case Study on Jumadi's Victory - Tika Maya Sari; Ian Pasaribu; Galank Pratama; Dimas Rizal (JURNAL KUASA, 2025)
This study analyzes Jumadi's campaign strategy and victory in the 2024 Kerinci Regency Regional People's Representative Council (DPRD) Legislative Election. This study explains, how Jumadi as a newcomer to politics with a background as a young entrepreneur, was able to achieve victory despite having no prior political experience. This study uses a qualitative approach with primary and secondary data obtained through interviews and documentation. The results indicate that Jumadi's victory was influenced by the implementation of an effective political marketing strategy based on Niffenegger's 4P framework: product, promotion, price, and place. The product aspect emphasized his image as a responsive and community-oriented leader with a focus on human resource development in the agricultural sector. The promotion aspect was carried out through direct outreach to the community, the use of social media, and the installation of billboards and posters. The price aspect reflected a positive reputation and personal credibility, while the place aspect related to voter mapping and mobilization of the support base through the Golkar Party's political machinery. These findings suggest that personal closeness, public trust, and the right political marketing strategy can be determining factors in the victory of new legislative candidates at the local level.